Uncovering how major extracellular proteins drive virulence and functional compensation in the mollusk pathogen Vibrio europaeus - Clara Martínez; Sergio Rodriguez; Alba Trueba; Diego Rey-Varela; Alicia E. Toranzo; Ana L. Dieguez; Javier Dubert (Journal of Invertebrate Pathology, 2026)

Metaproteomic insights into salinity’s impact on carbon assimilation and polyhydroxyalkanoate production in mixed cultures of purple phototrophic bacteria - Jose Ramon Lorenzo-Llarena; Alba Trueba-Santiso; Anuska Mosquera-Corral; Alba Pedrouso (Bioresource Technology, 2025)

Deciphering the constraints of pure bacterial strains for the complete catabolism of sulfamethoxazole: A proteomic and kinetic study - Ana P. Lopez Gordillo; Alba Trueba-Santiso; Kilian E. C. Smith; Andreas Schäffer; Juan M. Lema (Biodegradation, 2025)
Organic micropollutants (OMP) pose a significant environmental challenge, and microbial degradation research typically involves monitoring parent compound depletion and metabolite production. Previous studies on the antibiotic sulfamethoxazole (SMX) have shown its incomplete biotransformation by either mixed microbial communities or acclimated pure bacterial across various concentrations. However, the mechanisms behind this incomplete degradation and its relationship with the enzymatic capacities and expressions at environmentally relevant concentrations remain unclear. Therefore, this study investigated the biotransformation of SMX and the variations in the proteome at low µg L −1 concentrations using acclimated Microbacterium sp. BR1 as the bacterial degrader. Results show an incomplete depletion of the SMX and accumulation of the metabolite 3-amino-5-methylisoxazole (3A5MI). All test concentrations triggered the expression of the sulfonamide degrading enzymes (SadAB) and the modified target enzyme (Sul). Analysis of the functional proteins revealed increased cellular regulation and confirmed the bacterial strain's continued activity throughout the experiment. This suggests that at low SMX concentrations, even a highly sensitive and metabolically active strain may still require complementary enzymatic machinery to degrade potentially inhibitory metabolites. Thus, this study provides important insights into the persistence of SMX and reveals the complexities of antibiotic biodegradation at environmentally relevant concentrations, highlighting the need for comprehensive understanding of enzymatic mechanisms in micropollutant remediation strategies.

Ciprofloxacin biotransformation during anaerobic digestion: Major transformation products elucidation and environmental proteomics - Alba Trueba-Santiso; Matías Rivadulla; Oriol Casabella-Font; Elisabeth Cuervo-Lumbaque; Jelena Radjenovic; Francisco Omil; Sonia Suárez (Journal of Hazardous Materials, 2025)

Reliable methodology to determine biotransformation of PBAT in anaerobic conditions - Alba Trueba-Santiso; Reinhard Wimmer; Mathias Eskildsen; Juan Cubero-Cardoso; Juan M. Lema; Jeppe Lund Nielsen (Bioresource Technology, 2025)

Dual C–Cl isotope fractionation offers potential to assess biodegradation of 1,2-dichloropropane and 1,2,3-trichloropropane by Dehalogenimonas cultures - Alba Trueba-Santiso; Clara Torrentó; Jesica M. Soder-Walz; David Fernández-Verdejo; Mònica Rosell; Ernest Marco-Urrea (Chemosphere, 2024)

Environmental proteomics as a useful methodology for early-stage detection of stress in anammox engineered systems - Víctor Guzmán-Fierro; Alberto Dieguez-Seoane; Marlene Roeckel; Juan M. Lema; Alba Trueba-Santiso (Science of The Total Environment, 2024)

Metalloenzymes play major roles to achieve high-rate nitrogen removal in N-damo communities: Lessons from metaproteomics - Silvana Quiton-Tapia; Alba Trueba-Santiso; Juan M. Garrido; Sonia Suarez; Francisco Omil (Bioresource Technology, 2023)

Assessing labelled carbon assimilation from poly butylene adipate-co-terephthalate (PBAT) monomers during thermophilic anaerobic digestion - Jan Struckmann Poulsen; Alba Trueba-Santiso; Juan M. Lema; Simon Gregersen Echers; Reinhard Wimmer; Jeppe Lund Nielsen (Bioresource Technology, 2023)

Proteogenomics of the novel Dehalobacterium formicoaceticum strain EZ94 highlights a key role of methyltransferases during anaerobic dichloromethane degradation - Kenneth Wasmund; Alba Trueba-Santiso; Teresa Vicent; Lorenz Adrian; Stéphane Vuilleumier; Ernest Marco-Urrea (Environmental Science and Pollution Research, 2023)
Dichloromethane (DCM, methylene chloride) is a toxic, high-volume industrial pollutant of long-standing. Anaerobic biodegradation is crucial for its removal from contaminated environments, yet prevailing mechanisms remain unresolved, especially concerning dehalogenation. In this study, we obtained an assembled genome of a novel DCM-degrading strain, Dehalobacterium formicoaceticum strain EZ94, from a stable DCM-degrading consortium, and we analyzed its proteome during degradation of DCM. A gene cluster recently predicted to play a major role in anaerobic DCM catabolism (the mec cassette) was found. Methyltransferases and other proteins encoded by the mec cassette were among the most abundant proteins produced, suggesting their involvement in DCM catabolism. Reductive dehalogenases were not detected. Genes and corresponding proteins for a complete Wood-Ljungdahl pathway, which could enable further metabolism of DCM carbon, were also found. Unlike for the anaerobic DCM degrader “ Ca . F. warabiya,” no genes for metabolism of the quaternary amines choline and glycine betaine were identified. This work provides independent and supporting evidence that mec -associated methyltransferases are key to anaerobic DCM metabolism.